TMPRSS2 and COVID-19: Serendipity or Opportunity for Intervention? - Stopsack, Konrad H.; Mucci, Lorelei A.; Antonarakis, Emmanuel S.; Nelson, Peter S.; Kantoff, Philip W. (Cancer discovery, 2020)
TMPRSS2 is both the most frequently altered gene in primary prostate cancer and a critical factor enabling cellular infection by coronaviruses, including SARS-CoV-2. The modulation of its expression by sex steroids could contribute to the male predominance of severe infections, and given that TMPRSS2 has no known indispensable functions, and inhibitors are available, it is an appealing target for prevention or treatment of respiratory viral infections.